2020
DOI: 10.1186/s43088-020-0034-8
|View full text |Cite
|
Sign up to set email alerts
|

The association of estrogen-signaling pathways and susceptibility to open-angle glaucoma

Abstract: Background: Glaucoma is a complex multivariate disorder characterized by retinal ganglion cell (RGC) loss and optic nerve degeneration. Evidence suggests the role of estradiol (E 2) and the etiology of glaucoma. Therefore, this present study evaluates the association between estrogen-signaling pathways and the risk of open-angle glaucoma (OAG). Results: Meta-analysis was performed from available studies that investigated intraocular pressure (IOP) in patients treated with or without hormone replacement therapy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 39 publications
0
8
0
Order By: Relevance
“…The I 2 values indicated no (0-24.9%), low (25-49.9%), moderate (50-74.9%) or high (75-100%) heterogeneity. The random-effect model (REM) was used if heterogeneity existed; otherwise, the fixed-effect model (FEM) was used 250,[276][277][278][279][280][281][282][283][284][285][286][287] . Subgroup analysis was stratified by type of disease and ethnicity or racial descent.…”
Section: Methodsmentioning
confidence: 99%
“…The I 2 values indicated no (0-24.9%), low (25-49.9%), moderate (50-74.9%) or high (75-100%) heterogeneity. The random-effect model (REM) was used if heterogeneity existed; otherwise, the fixed-effect model (FEM) was used 250,[276][277][278][279][280][281][282][283][284][285][286][287] . Subgroup analysis was stratified by type of disease and ethnicity or racial descent.…”
Section: Methodsmentioning
confidence: 99%
“…Meta-analysis for each gene polymorphism was performed for two or more studies, as previously described [ 3 , 4 , 5 , 6 , 22 , 23 , 24 , 25 ]. Genotypic frequency of GPER gene polymorphism was tested for deviation from the Hardy–Weinberg equilibrium (HWE) in the control subjects if HWE was not reported.…”
Section: Methodsmentioning
confidence: 99%
“…Genotypic frequency of GPER gene polymorphism was tested for deviation from the Hardy–Weinberg equilibrium (HWE) in the control subjects if HWE was not reported. The genetic association was examined using different genetic models, including allelic (a vs. A), recessive (aa vs. Aa + AA), dominant (aa + Aa vs. AA), over dominant (Aa vs. aa + AA), homozygous (aa vs. AA), and heterozygous (Aa vs. AA) models [ 5 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 ]. The associations between GPER gene polymorphisms or GPER expression levels with cancer predisposition and progression were calculated by the pooled odds ratio (OR) and 95% confidence interval (CI).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“… 9 Besides, a recent meta-analysis study reported a significant association of the estrogen signaling pathway in open-angle glaucoma with a protective effect of hormone replacement therapy in lowering IOP. 70 Furthermore, EEIG1 (FAM102A) was demonstrated to serve as a novel receptor activator of NF-κB (RANK) signaling component with a role in osteoclast formation, 71 suggesting its role in tissue maintenance, repair, and remodeling. Besides, PIP5KL1 (Phosphatidylinositol-4-phosphate 5-kinase-like 1) was also found to be the nearby gene on this loci 20 that has been reported to inhibit cell proliferation and migration and may have a role in tumorigenesis.…”
Section: Genome-wide Association Studies In Pacgmentioning
confidence: 99%